(untitled) (Journal of Asian Development Studies, 2025)
The banking sector in Pakistan faces increasing challenges in sustaining customer loyalty due to heightened competition, digital transformation, and evolving consumer expectations. This study examines the role of relationship marketing and service quality in fostering customer retention, explicitly focusing on trust, engagement, and goal attainment. Utilizing the SERVQUAL model, Commitment-Trust Theory, and Unified Theory of Acceptance and Use of Technology (UTAUT), the research explores the interplay between service quality, digital banking adoption, and cultural influences in shaping customer behavior. A quantitative methodology was employed through a structured survey, collecting data from banking customers across Pakistan. The study utilized Structural Equation Modeling (PLS-SEM) to analyze the mediating and moderating effects of customer satisfaction, engagement, and cultural differences on retention. The findings reveal that customer trust and financial goal attainment significantly influence retention, while service quality exhibits a weaker impact. Additionally, engagement through digital banking positively affects satisfaction but does not directly drive loyalty. The results suggest banks must prioritize transparent practices, ethical banking, and personalized financial solutions to enhance retention. The study challenges traditional service quality models, emphasizing the growing importance of digital trust and customer-centric financial planning. Practical implications highlight the need for AI-driven banking experiences, predictive analytics, and hybrid customer service models that balance automation with relationship marketing. This research contributes to the evolving discourse on banking loyalty strategies and offers insights into optimizing retention in Pakistan’s financial sector.